HUBUNGAN PEMAAFAN DAN KECEMASAN PADA PESERTA DIDIK REMAJA MUSLIM DENGAN ORANG TUA BERCERAI - Jalal, Novita Maulidya; Eka Sufartianingsih Jafar (Indonesian Journal of Islamic Studies (IJIS), 2025)
Parental divorce can lead to emotional and psychological disturbances in children, especially during adolescence. The aim of this study is to examine the relationship between forgiveness and anxiety in adolescents with divorced parents. This research uses a quantitative method. The number of subjects in this study was 35 adolescents with divorced parents, aged between 15 and 25 years, moeslem students. The sampling technique used was incidental sampling. The instruments used were a forgiveness questionnaire and an anxiety questionnaire. Data were analyzed using correlation techniques. The results of the study showed a significant correlation between forgiveness and anxiety. Thus, it can be concluded that there is a relationship between forgiveness and anxiety in adolescents with divorced parents. The implication of this research is that it can be used to help adolescents with divorced parents become more capable of engaging in the forgiveness process regarding their parents' divorce